The Innovation of Tofu Waste Liquid Biogas Reactor Technology as an Alternative Energy Resource - Nely Ana Mufarida; Asroful Abidin (Diponegoro University, 2021)
Abstract - Increased production capacity of the tofu factory has an impact on increasing waste. Tofu liquid waste is one of the untapped wastes and even just thrown away. Besides, the tofu industry needs water for its processing, so more wastewater produces more than tofu solid waste. Wastewater from the making tofu process produces liquid waste which is a source of pollution for humans and the environment that will disrupt the ecosystem and environmental health.The right process for handling tofu wastewater is by an anaerobic process that converts the liquid waste fermented by bacteria into methane gas. This methane gas can be used as a new energy resource and this energy can be used for cooking or frying tofu.The results of the research are from 500 liters of tofu liquid waste treated, 149.6 liters of biogas were obtained in 21 days. It increased the quality of biogas as seen from the increase in CH4 levels by 70%, temperature in the digester by 32oC, volume in 149.6 liters, and decreasing H2S levels by 9 ppm, CO by 13 ppm, O2 by 15.1%. Based on the test results, the maximum fermentation time is 21 days.